2014 International Conference on Communication and Signal Processing 2014
DOI: 10.1109/iccsp.2014.6949915
|View full text |Cite
|
Sign up to set email alerts
|

Improved BDD compression by combination of variable ordering techniques

Abstract: Variable ordering is the most important task done with the Binary Decision Diagrams (BDDs) in order to reduce their size. Many researchers have proposed different algorithms for variable ordering for reduction in size of BDDs. This paper presents an innovative technique by combining the variable ordering algorithms available to get the best possible minimum sized BDDs. Colorado University Decision Diagram (CUD D)package is used as the tool for the process. Testing is carried out on the ISCAS benchmark circuits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…For example, a verification tool-set called ITS-tools by Y. Thierry-mieg [107] has been developed based on symbolic model checking which supports reachability property and two kinds of temporal logic CTL and LTL of concurrent specification. Another symbolic-based model checker has been provided by R. Cavada et al [99] for verifying finite-states and infinite-states synchronous systems.…”
Section: Classification Of State Space Reduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a verification tool-set called ITS-tools by Y. Thierry-mieg [107] has been developed based on symbolic model checking which supports reachability property and two kinds of temporal logic CTL and LTL of concurrent specification. Another symbolic-based model checker has been provided by R. Cavada et al [99] for verifying finite-states and infinite-states synchronous systems.…”
Section: Classification Of State Space Reduction Methodsmentioning
confidence: 99%
“…They demonstrated that using graph representation of a given Boolean function and computing shortest path among the variables can improve ROBDD. Further work to improve ROBDD presented by P. K. Sharma et al [99] to get the most optimum size of ROBDD. However, computing an optimum order for ROBDD generally falls into NP-Complete problem category proved by B. Bolling et al in [19] and B. Bolling in [18].…”
Section: Classification Of State Space Reduction Methodsmentioning
confidence: 99%
“…They demonstrated that using a graph representation of a given Boolean function and computing the shortest path among the variables can improve ROBDD. Further work to improve ROBDD was presented by P. K. Sharma et al [55] to get the most optimum size of ROBDD. However, computing an optimum order for ROBDD generally falls into the NP-Complete problem category proved by B. Bolling et al in [56] and B. Bolling in [57].…”
Section: A: Symbolic Model Checkingmentioning
confidence: 99%